Oral contrast enhanced bowel ultrasonography in the assessment of small intestine Crohn's disease. A prospective comparison with conventional ultrasound, x ray studies, and ileocolonoscopy. Issue 11 (11th October 2004) - Parente, F; Greco, S; Molteni, M; Anderloni, A; Sampietro, G M; Danelli, P G; Bianco, R; Gallus, S; Bianchi Porro, G
Abstract : Background/Aim: Although ultrasound (US) has proved to be useful in intestinal diseases, barium enteroclysis (BE) remains the gold standard technique for assessing patients with small bowel Crohn's disease (CD). The ingestion of anechoic non-absorbable solutions has been recently proposed in order to distend intestinal loops and improve small bowel visualisation. The authors' aim was to evaluate the accuracy of oral contrast US in finding CD lesions, assessing their extent within the bowel, and detecting luminal complications, compared with BE and ileocolonoscopy. Methods: 102 consecutive patients with proven CD, having undergone complete x ray and endoscopic evaluation, were enrolled in the study. Each US examination, before and after the ingestion of a polyethylene glycol (PEG) solution (500–800 ml), was performed independently by two sonographers unaware of the results of other diagnostic procedures. The accuracy of conventional and contrast enhanced US in detecting CD lesions and luminal complications, as well as the extent of bowel involvement, were determined. Interobserver agreement between sonographers with both US techniques was also estimated. Results: After oral contrast, satisfactory distension of the intestinal lumen was obtained in all patients, with a mean time to reach the terminal ileum of 31.4 (SD 10.9) minutes. Overall sensitivity of conventional and oral contrast US in detecting CD lesions were 91.4% and 96.1%, respectively. The correlation coefficient between US and x ray extent of ileal disease was r 1  = 0.83 (p<0.001) before and r 2  = 0.94 (p<0.001) after PEG ingestion; r 1 versus r 2 p<0.01. Sensitivity in detecting strictures was 74% for conventional US and 89% for contrast US. Overall interobserver agreement for bowel wall thickness and disease location within the small bowel was already good before but significantly improved after PEG ingestion. Conclusions: Oral contrast bowel US is comparable with BE in defining anatomic location and extension of CD and superior to conventional US in detecting luminal complications, as well as reducing interobserver variability between sonographers. It may be therefore regarded as the first imaging procedure in the diagnostic work up and follow up of small intestine CD.